Ageing Management of Nuclear Power Plants during Delayed Construction Periods, Extended Shutdown and Permanent Shutdown Prior to Decommissioning - IAEA (IAEA-TECDOC., 2021)
S part of the IAEA programme on International Generic Ageing Lessons Learned (IGALL), this publication provides a summarized description of internationally accepted practices. Examples of the national approaches to ageing management for the specific periods of extended shutdown, delayed construction and post final shutdown as applied in the nuclear power plants of participating IGALL Member States are presented. In addition, some of the information is also applicable for the evaluation of ageing effects prior to and after restarting operation. The publication complements existing IAEA publications on ageing management approaches of Member States during normal operation and is intended for use by regulatory bodies, operating organizations, manufacturers, designers and technical support organizations.